2015
DOI: 10.1371/journal.pone.0139224
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+-Regulation of the Mitochondrial External NADPH Dehydrogenase in Plants Is Controlled by Cytosolic pH

Abstract: NADPH is a key reductant carrier that maintains internal redox and antioxidant status, and that links biosynthetic, catabolic and signalling pathways. Plants have a mitochondrial external NADPH oxidation pathway, which depends on Ca2+ and pH in vitro, but concentrations of Ca2+ needed are not known. We have determined the K0.5(Ca2+) of the external NADPH dehydrogenase from Solanum tuberosum mitochondria and membranes of E. coli expressing Arabidopsis thaliana NDB1 over the physiological pH range using O2 and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
2
5
0
Order By: Relevance
“…A particularly striking example for intracellular pH regulation in plant cells is provided by the external mitochondrial NAD(P)H DEHYDROGENASE B1, which contributes to the alternative respiratory pathway and was shown to be stimulated by increases in [Ca 2+ ] cyt . However, biochemical data revealed that the enzyme is only sensitized to Ca 2+ regulation by a coincident decrease of pH (Hao et al, 2015). Our data now reveal that, in vivo, those changes coincide, providing the physiological basis for active regulation of the NADPH oxidation pathway to occur.…”
Section: Discussionsupporting
confidence: 51%
“…A particularly striking example for intracellular pH regulation in plant cells is provided by the external mitochondrial NAD(P)H DEHYDROGENASE B1, which contributes to the alternative respiratory pathway and was shown to be stimulated by increases in [Ca 2+ ] cyt . However, biochemical data revealed that the enzyme is only sensitized to Ca 2+ regulation by a coincident decrease of pH (Hao et al, 2015). Our data now reveal that, in vivo, those changes coincide, providing the physiological basis for active regulation of the NADPH oxidation pathway to occur.…”
Section: Discussionsupporting
confidence: 51%
“…4B). Figure 4C shows that NADPH dehydrogenase activity did not respond to high concentrations of calcium, as occurs in other fungal systems such as N. crassa and some plants [41,44]. As both the mRNA and the protein with the calcium binding domain (um03669) were synthesized in the four culture conditions, the lack of an effect of calcium on the respiratory activity of permeabilized cells is in agreement with the absence of critical residues in the putative calcium binding domain of this protein.…”
Section: Primerssupporting
confidence: 68%
“…The oxidation of NADH was shown to specifically require Ca 2+ (Møller et al, 1981b) and NADPH oxidation was also inhibited by chelators of divalent cations Edwards, 1979, 1980;Møller and Palmer, 1981). The activities of NADH and NADPH oxidation are regulated by submicromolar and micromolar concentrations of cytosolic free Ca 2+ , respectively, and activation of NADPH oxidation by Ca 2+ depends on the cytosolic pH (Hao et al, 2015). The concentration of the second messenger Ca 2+ , which has a central role in plant metabolism (Hetherington and Brownlee, 2004), also changes with cytosolic pH (Behera et al, 2018).…”
Section: External Nad(p)h Dehydrogenasesmentioning
confidence: 97%